Design of Education Application based on Shiva 3D Platform - Sun, Hui (International Journal of Emerging Technologies in Learning (iJET), 2017)
With the popular spread of electronic products, more and more related applications based on a virtual platform are being utilized. Meanwhile, more and more concerns are surfacing about the implementation of the functionality of virtual reality technology in the education or training field. The paper gives a specific example to propose the characteristics of a gaming education application based on Shiva 3D game engine. The implementation of this kind of application indicates that virtual reality technology of video games can be used in self-learning in education and training and can have significant results.